A RETROSPECTIVE AND PROSPECTIVE STUDY FOR ADVERSE DRUG REACTION OF CANCER CHEMOTHERAPY IN BREAST CANCER - Saini, Saket Saini; Zia, Alishan; Tyagi, Shaily; Nautiyal, Himani (International Journal of Research -GRANTHAALAYAH, 2022)
Cancer is the major health problem worldwide, according to WHO in 2018 cancer is responsible for an estimated 9.6 mill death out of 18.1 million new cases and globally 6 deaths occur due to cancer. Cancer is the abnormal, unwanted growth of cells, when abnormal cells divide in an uncontrolled way within the body and destroy normal tissue that can lead to death. Normal body cell grows, divide, and die in an orderly way or cancer cells are different because they do not die, grow continuously, and divide in orderly way. There are more than 200 types of cancer. Any agent that converts a body cell to develop abnormally can cause cancer. The cancer causative agents include- radiations, chemical or toxic compound exposure, lifestyle, hormones, and human genetics. Most tumors can be categorized as one of the three main groups: carcinomas, sarcomas and leukemia or lymphomas. Carcinomas, which associated around 90% of human cancer, are malignancies of epithelial cell. Sarcomas, which are uncommon in human, are solid tumor of connective tissue including muscle, bone, cartilage, and fibrous tissue. Leukemia and lymphomas, which represent around 8% of human malignancies, emerge from the blood forming cell and from cell of immune system. Carcinoma of breast is a malignant disease with variable outcomes. Breast carcinoma is second most common cause of death in females though it can also occur in men but are very uncommon. This type of cancer is malignant cell growth in breast. This study was done to compare and analyze adverse drug reactions of cancer chemotherapy in breast cancer in a rural hospital. Objectives included- a) To study adverse drug reactions of various chemotherapeutic agents used in patients suffering breast cancer b) To compare various side-effects as a result of different combination protocols to identify the drug protocol with least amounts of adverse drug reactions. However, an extremely significant difference was found between all of the comparison groups studied.